DIMORFISME SEKSUAL DAN RASIO SEKSUAL JENDERDUA JENIS IRAN ARWANA ASIA {Scleropages jardinii dan S.formosus : Osteoglossidae) - Tjakrawidjaja, Agus H (BERITA BIOLOGI, 2006)
Study on biological reproduction aspects of Asian Arwanas fishes {Scleropages jardinii and S. formosus) particularly their sexual dimorphism and sexual ratio of gender is very important as a base for captivity breeding. Up to the present, it is difficult to determine the sexual identity of these Asian Arwanas, lead the difficulties in making sexual ratio description.The reliable sexual ratio in captive breeding would increase the production. The result of this research would be useful for reference in the identification of the gender of Asian Arwanas.